2016
DOI: 10.1542/peds.2016-1890
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Serogroup B Meningococcal Vaccine for Persons 10 Years and Older

Abstract: This policy statement provides recommendations for the prevention of serogroup B meningococcal disease through the use of 2 newly licensed serogroup B meningococcal vaccines: MenB-FHbp (Trumenba; Wyeth Pharmaceuticals, a subsidiary of Pfizer, Philadelphia, PA) and MenB-4C (Bexsero; Novartis Vaccines, Siena, Italy). Both vaccines are approved for use in persons 10 through 25 years of age. MenB-FHbp is licensed as a 2- or 3-dose series, and MenB-4C is licensed as a 2-dose series for all groups. Either vaccine is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…15 It suggested that Category B recommendations should be considered in the context of a clinician-patient interaction and that discussion include the balance between desirable (benefits, savings) and undesirable effects (harms, costs) of the vaccine in question. Although the AAP’s Committee on Infectious Diseases 16 has more directly addressed how to discuss the MenB vaccine specifically, additional guidance about how to communicate with patients and families about Category B recommendations in general is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…15 It suggested that Category B recommendations should be considered in the context of a clinician-patient interaction and that discussion include the balance between desirable (benefits, savings) and undesirable effects (harms, costs) of the vaccine in question. Although the AAP’s Committee on Infectious Diseases 16 has more directly addressed how to discuss the MenB vaccine specifically, additional guidance about how to communicate with patients and families about Category B recommendations in general is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies directed against fHbp are bactericidal, and can both activate the complement cascade, and block the recruitment of fH by bacteria [5, 6, 913]. fHbp is included in licensed protein-based vaccines against group B meningococcus [14, 15]. …”
Section: Introductionmentioning
confidence: 99%
“…In general, this consists of one dose of MenACWY (for protection against serogroups A, C, W, and Y) at age 11 with a booster dose at age 16 [49]. Serogroup B meningococcal vaccine (MenB) can be considered starting at age 16, especially during outbreaks and for students living in residency halls [50]. There is very little information on the immunogenicity of meningococcal vaccines in SOT recipients.…”
Section: Meningococcal Vaccinesmentioning
confidence: 99%
“…High-risk children older than 10 years should additionally receive MenB [54]. Patients receiving eculizumab should receive both MenACWY and MenB at the initiation of treatment [50]. KT candidates and recipients who are at high risk of invasive meningococcal infections should receive boosters of MenACWY every 5 years [53].…”
Section: Meningococcal Vaccinesmentioning
confidence: 99%